BENEFICIAL EFFECT OF NISHAAKATHAKAADHI KASHAYAM ON STREPTOZOTOCIN INDUCED DIABETES AND GLUCOSE METABOLIC ENZYMES - Yuvaraj, P.; Shine Paul, *Ann; Varghese, Joy; Jolly, C.I (International Journal of Ayurveda and Pharma Research, 2017)
Polyherbal traditional formulation Nishaakathakaadhi Kashayam elicit antihyperglycemic effects in streptozotocin induced hyperglycemic rats. Nishaakathakaadhi Kashayam 0.6 ml/kg, p.o. significantly reduced the fasted blood glucose level after 60 days of treatment in diabetic rats. The Kashayam also reduced serum cholesterol, triglycerides, LDL, VLDL, alanine transaminase, aspertate transaminase, alkaline phophatase and urea whereas increased HDL, albumin, protein and haemoglobin levels become normal after the treatment. Glycolytic enzyme showed a significant increases in Streptozotocin induced condition while a significant decrease were observed in levels of the gluconeogenic enzymes in Nishaakathakaadhi Kashayam treated diabetic rats. The Kashayam was non-significantly active with standard drug Glibenclamide (0.6 mg/kg, p.o.). The Kashayam has a positive effect on the histopathological changes of the pancreatic beta cells in Streptozotocin induced diabetic rats. The results suggest that Nishaakathakaadhi Kashayam possesses potential antihyperglycemic effect by regulating glucose homeostasis in streptozotocin induced diabetic rats. The scientific evidences to antidiabetic use suggest that administration of polyherbal formulation to rats, in a dosage used safely by humans, reduces the production of various diabetes causing biochemical parameters and concomitantly prevents the development of Type 2 (NIDDM) diabetes in established animal models. A combination of different herbals in NKK is used to get the enhanced desired activity.